2022
DOI: 10.1002/ece3.8903
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial comparison of food web structure in marine pastures in the Pearl River Estuary: Implications for sustainable fisheries management

Abstract: The biological and ecological integrity of marine ecosystems in the Pearl River Estuary (PRE) has been compromised due to overfishing and water pollution. Fishing moratorium and artificial reef construction have been implemented in Wanshan and Miaowan for resource protection and restoration. Therefore, food web structure and trophic pathways of Wanshan, Miaowan, and Wailingding in different temporal and spatial situation will be determined using the Ecopath model, as well as the keystone species affecting thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…It was well noted that a fishing moratorium provides benefits by facilitating the restoration of fishery resources in the short term, which would mainly restore the short life cycle organisms at low trophic levels. 22 Previous research showed that improving predation conditions and expanding the distributed scope were necessary for the sole cetacean Yangtze finless porpoise (Neophocaena asiaeorientalis). 46 Therefore, the ten-year fishing ban in the Yangtze River was implemented in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was well noted that a fishing moratorium provides benefits by facilitating the restoration of fishery resources in the short term, which would mainly restore the short life cycle organisms at low trophic levels. 22 Previous research showed that improving predation conditions and expanding the distributed scope were necessary for the sole cetacean Yangtze finless porpoise (Neophocaena asiaeorientalis). 46 Therefore, the ten-year fishing ban in the Yangtze River was implemented in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Here, socio-economic indexes were analyzed together, and it was found that fishing was one of the key drivers of the fish diversity decline in the Pearl River. Previous studies (focusing on fishery resources and fish communities) had reported that large dynamics of the fishery ecosystem in subtropical rivers and lakes were caused by overfishing, , and the response strategy of different ichthyological groups to overfishing events varied along with feeding structure and trophic level changes. During the past forty years, a steep decrease in fish and dietary organism diversity was observed in the Pearl River, which was consistent with the decrease in the fish, interaction density, and food web indexes (system omnivory index, Finn’s cycling index, and MPL ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen fish species were identified including Cynoglossus joyneri ( n = 4), Cynoglossus macrolepidotus ( n = 2), Moolgarda cunnesius ( n = 3), Nemipterus japonicus ( n = 4), Siganus fuscescens ( n = 2), Ambassis urotaenia ( n = 3), Collichthys lucidus ( n = 3), Ilisha elongata ( n = 3), Leiognathus brevirostris ( n = 6), Johnius belangerii ( n = 5), Trypauchen vagina ( n = 4), Thryssa kammalensis ( n = 4), Sillago sihama ( n = 1), Dendrophysa russelii ( n = 3), Platycephalus indicus ( n = 2), Muraenesox talabonoides ( n = 1), and Argyrosomus argentatus ( n = 3). The collected components that could form an estuarine food web in this study were mainly dominated by benthic species (Table S2), all of which represent typical estuarine species in the PRE ecosystem. ,, After collection, the samples were transported to the laboratory and stored in a refrigerator at −20 °C. In addition, 21 surface water samples and 10 surface sediment samples were collected from the sampling region.…”
Section: Methodsmentioning
confidence: 99%
“…Recognition and categorization of biota samples were based on databases such as China Animal Science Database, EOL, Fishbase, SeaLifeBase, and WoRMS . Based on previous reports, these biota samples collected in this study belonged to the representative species of the PRE. To minimize the microbial activity and transformation of targeted chemicals, the pH of water samples was acidified to 3.0 immediately upon collection, and 1 mL of glutathione solution (1 M) and 5% methanol (v/v) were added. , All samples were preserved in a −20 °C refrigerator and then delivered to the laboratory promptly. Information on sampling locations, water quality, and biota samples is provided in Figure S1 and Tables S2–S4 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%